Zihinsel engelli çocuğu olan annelere verilen farkındalık temelli beceri eğitiminin farkındalık düzeyi üzerine etkisi - İnan Budak, Merve (My University, 2024)
Amaç: Bu araştırma ‘’Bilinçli Farkındalık Temelli Stresi Azaltma temel alarak hazırlanmış grup beceri eğitim programının zihinsel engelli çocuğu olan annelerde stres düzeyi, bilinçli farkındalık ve duygu düzenleme becerileri üzerine etkinliğini belirlemeyi amaçlamaktadır Gereç ve Yöntem: Bu araştırma, ön test son test, 3. ve 6. ay izlemli tek grup yarı deneysel desende yürütülmüştür. Araştırmaya katılan annelere 6 haftalık bilinçli farkındalık temelli grup beceri eğitim uygulanmıştır. Oturumlar ortalama 90 dakika sürmüştür. Araştırma 43 anne ile başlamıştır. 5 anne COVID-19 sebebiyle kayıp yaşadığı için eğitimler esnasında ayrılmıştır (n=38). 3. ay izlem ölçümünde 6 anne ölçüm araçlarını eksik doldurmuştur. 6. ay izlem ölçümünde de 1 annenin izlem ölçümünü yapmaması nedeniyle analizler 31 veri üzerinden yapılmıştır. Bulgular: Katılımcıların Algılanan Stres Ölçeği puanlarında ön test ve son testte istatistiksel olarak anlamlı bir fark bulunmuştur. Bilinçli Farkındalık Ölçeği puanı ve Bilişsel Duygu Düzenleme Ölçeği puanında başlangıç ve takipler arasında istatistiksel olarak anlamlı bir fark bulunmamıştır. Sonuç: Bilinçli farkındalık temelli grup beceri eğitiminin zihinsel engelli çocuğu olan annelerin stres düzeyleri üzerinde etkisinin olduğu bulunmuştur. Bu çalışma uluslararası literatürde COVID-19 döneminde zihinsel engelli çocuğu olan annelere verilen bilinçli farkındalık temelli eğitimin etkinliğinin incelendiği ilk araştırmadır. Ulusal olarak bu araştırma daha önce çalışılmamıştır. Bu sebeple bu araştırma ulusal alanda gelecekte yapılacak çalışmalar için yol gösterici nitelikte olabilir.

Aim: This study aims to determine the effectiveness of a group skills training programme based on the Mindfulness-Based Stress Reduction Programme on stress level, mindfulness and emotion regulation skills in mothers of children with intellectual disability. Materials and Method: This study was conducted in a single group quasi-experimental design with pre-test post-test, 3rd and 6th month follow-up. A 6-week mindfulness-based group skills training programme was applied to the mothers participating in the study. The sessions lasted 90 minutes on average. The research started with 43 mothers. 5 mothers were separated during the trainings due to loss due to COVID-19 (n=38). In the 3rd month follow-up measurement, 6 mothers completed the measurement tools incompletely. In the 6th month follow-up measurement, 1 mother did not complete the follow-up measurement, so the analyses were performed on 31 data. Results: A statistically significant difference was found in the Perceived Stress Scale scores of the participants in the pretest and posttest. There was no statistically significant difference in the Mindful Attention Awareness Scale score and Cognitive Emotion Regulation Questionnaire score between baseline and follow-up. Conclusion: Mindfulness-based group skills training was found to have an effect on the stress levels of mothers of children with intellectual disability. This study is the first study in the international literature to examine the effectiveness of mindfulness-based training given to mothers of children with intellectual disability during the COVID-19 period. Nationally, this research has not been studied before. For this reason, this study may be a guide for future studies in the national field.
The effect of mindfulness-based skills training given to mothers with children with ıntellectual disabilities on mindfulness level
Keywords: anne; Beceri eğitimi; bilinçli farkındalık; child with intellectual disability; Children with mental disabilities; Hemşirelik; mindfulness; mother; Nursing; stres Skills training; stress; zihinsel engelli çocuk; Zihinsel engelli çocuklar